(untitled) (Research, Society and Development, 2020)
Objective: This study aimed to analyze the Brazilian scientific production on the use of low-level laser therapy (LLLT) in the prevention and treatment of oral mucositis in patients undergoing cancer treatment. Methodology: This was a cross-sectional and observational study, with a quantitative approach based on secondary data. A research was carried out in the annals of the meetings of the Brazilian Society of Dental Research (SBPqO), in the period from 2009 to 2019, locating the following keywords: “Laser” and “Mucositis”. Based on the criteria used, all abstracts containing the terms were identified using the program’s search tool. Results: After analysis and reading, obeying the inclusion and exclusion criteria, 33 abstracts were included. Of the total evaluated, 21.2% (n = 7) of the abstracts were from studies using laser therapy in oral mucositis and were carried out in the year 2018. The Midwest region, especially the state of Goiás and specifically UFG, were the origin the largest number of published abstracts (33.3%). A total of 60.4% of the surveys had no aid or financing. Conclusion: Among the research published based on the summaries of the annual SBPqO meetings, it can be concluded that there was a slight increase in research using laser / photobiomodulation therapy for the treatment of oral mucositis in cancer patients, suggesting that laser therapy is a alternative therapeutic resource to assist in reducing adverse effects resulting from antineoplastic treatment.